How Ancient Europeans Saw the World : Vision, Patterns, and the Shaping of the Mind in Prehistoric Times - Wells, Peter S. S. (Princeton University Press, 2012)
Cover -- Contents -- List of Illustrations -- Preface -- Acknowledgments -- PART I: THEORY AND METHOD -- Chapter 1: Of Monsters and Flowers -- Chapter 2: Seeing and Shaping Objects -- Chapter 3: The Visual Worlds of Early Europe -- Chapter 4: Frame, Focus, Visualization -- PART II: MATERIAL: OBJECTS AND ARRANGEMENTS -- Chapter 5: Pottery: The Visual Ecology of the Everyday -- Chapter 6: Attraction and Enchantment: Fibulae -- Chapter 7: Status and Violence: Swords and Scabbards -- Chapter 8: Arranging Spaces: Objects in Graves -- Chapter 9: Performances: Objects and Bodies in Motion -- Chapter 10: New Media in the Late Iron Age: Coins and Writing -- PART III: INTERPRETING THE PATTERNS -- Chapter 11: Changing Patterns in Objects and in Perception -- Chapter 12: Contacts, Commerce, and the Dynamics of New Visual Patterns -- CONCLUSION -- Chapter 13: The Visuality of Objects, Past and Present -- Bibliographic Essay -- References Cited -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- V -- W -- X -- Z.